Stable, surfactant-free graphene–styrene methylmethacrylate composite for ultrafast lasers - Torrisi,F; Popa,D; Milana,S; Jiang,Z; Hasan,T; Lidorikis,E; Ferrari,AC (Advanced Optical Materials, 2016)
Graphene–polymer composites play an increasing role in photonic and optoelectronic applications, from ultrafast pulse generation to solar cells. The fabrication of an optical quality surfactant-free graphene-styrene methyl methacrylate composite, stable to large humidity and temperature ranges is reported. The composite is tailored for photonic applications showing wavelength-independent linear absorption in the visible and near-infrared. When tested in a mode-locked laser, it allows the generation of stable ≈326 fs mode-locked pulses at 1550 nm, unperturbed by environmental conditions. The composite continues to operate as a saturable absorber even under complete water immersion at 60 °C. This confirms its stability against high-temperature and humidity.